Decreased behavioural and neurochemical effects of angiotensin IV following prenatal alcohol exposure in the mouse. (October 2019) - Fidalgo, Sara; Patel, Mira; Quadir, Angela; Sadiq, Wafia; Gard, Paul R.
Abstract: Angiotensin IV (ang IV) is known to improve learning and memory in animal models but the mechanism is unclear. We have previously demonstrated sex differences in the pro-cognitive effects of ang IV, and that prenatal alcohol exposure (PAE) abolishes these effects. This study aimed to explore a possible mechanism underlying the sex differences and the effects of PAE in male mice. Mouse breeding harems received 5% ethanol in drinking water throughout pregnancy and lactation in a two-bottle schedule. The effects of ang IV were assessed in offspring at 4 months of age using the open field test, novel object recognition test and elevated plus maze. Aminopeptidase activity of brain insulin-regulated aminopeptidase (IRAP), a putative target of ang IV, was determined. As seen in a previous similar study, ang IV administered immediately after the second training trial significantly improved novel object recognition 24 h later in male mice but not female. PAE abolished this pro-cognitive effect in males. PAE also increased anxiety-like behaviour in male but not female offspring. Ang IV decreased the aminopeptidase activity of brain IRAP in control male, but not female, mice; PAE abolished this inhibitory effect. Ang IV improved memory consolidation in male but not female mice and PAE abolished this effect in the males. While the effects of PAE may be related to increased anxiety; ang IV decreased the aminopeptidase activity in male but not female mice and PAE abolished this inhibitory effect. The results therefore suggest that improvements in learning and memory induced by peripheral administration of ang IV correlate with a reduction of the enzyme activity of IRAP. This is the first demonstration that ang IV administered peripherally can induce long-term (24 h) changes in IRAP function which are probably not simple competitive inhibition and the first demonstration that PAE alters IRAP activity. Highlights: The pro-cognitive effect of angiotensin IV associated with reduction of aminopeptidase activity of insulin-regulated aminopeptidase in vivo . Prenatal alcohol exposure abolished the pro-cognitive effect of angiotensin IV Prenatal alcohol exposure prevents the effects of angiotensin IV on insulin-regulated aminopeptidase.